2020
DOI: 10.1371/journal.pone.0229033
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional feasibility study of neurovascular ultrasound in Malawian adults with acute stroke-like syndrome

Abstract: Background In sub-Saharan Africa, there is a dearth of epidemiologic data on the burden of cerebral atherosclerosis. This is explained by the limited availability and the high cost of standard vascular imaging techniques. Neurovascular ultrasound is portable, cheaper and non-invasive and could, therefore, represent a reasonable alternative to fill this knowledge gap. We explored the feasibility of neurovascular ultrasound in Malawian adults with acute stroke-like syndrome to inform the design of future large s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…We recommend future researchers to use a constant cutoff for comparability of study ndings or present the various percentages of CIMT abnormalities based on the various cutoffs. A Malawian study revealed the prevalence of thickened carotid intima thickness to be 18% which is slightly lower than in the present study [39]. The difference could be due to our study having a higher mean age of participants (62 years), a higher prevalence of hypertension (88%) compared to the Malawian study.…”
Section: Carotid Intima Thicknesscontrasting
confidence: 89%
See 1 more Smart Citation
“…We recommend future researchers to use a constant cutoff for comparability of study ndings or present the various percentages of CIMT abnormalities based on the various cutoffs. A Malawian study revealed the prevalence of thickened carotid intima thickness to be 18% which is slightly lower than in the present study [39]. The difference could be due to our study having a higher mean age of participants (62 years), a higher prevalence of hypertension (88%) compared to the Malawian study.…”
Section: Carotid Intima Thicknesscontrasting
confidence: 89%
“…Studies in sub-Saharan Africa involving high risk cerebrovascular patients document a carotid plaque prevalence of between 15-30 [20,21]. In a meta-analysis involving 64 studies, high risk echolucent plaques were present in high risk patients with carotid stenosis [39].…”
Section: Carotid Plaquesmentioning
confidence: 95%
“…However, a study in participants with hypertension and stroke in Nigeria found that carotid intima media thickness was a sensitive indicator of cardiovascular phenotype and had a stronger association with stroke than popular cardiovascular risk calculators that are used to estimate the time-related risk of cardiovascular disease 149 , 150 . A more recent study of individuals diagnosed with acute stroke-like syndrome in Malawi reported that 39.4% had extracranial atherosclerosis and 19.2% had intracranial atherosclerosis 151 . Post-mortem studies undertaken ~40 years apart also identified a temporal increase in the frequency and severity of cerebral atherosclerosis among Nigerian Africans in tandem with the overall rise in the burden of cardiovascular disease and stroke occurrence 152 154 .…”
Section: Stroke Phenotypes In Africamentioning
confidence: 99%